Beyond Auditory Sensory Processing Deficits: Lexical Tone Perception Deficits in Chinese Children With Developmental Dyslexia. (May 2018) - Tong, Xiuhong; Tong, Xiuli; King Yiu, Fung
Increasing evidence suggests that children with developmental dyslexia exhibit a deficit not only at the segmental level of phonological processing but also, by extension, at the suprasegmental level. However, it remains unclear whether such a suprasegmental phonological processing deficit is due to a difficulty in processing acoustic cues of speech rhythm, such as rise time and intensity. This study set out to investigate to what extent suprasegmental phonological processing (i.e., Cantonese lexical tone perception) and rise time sensitivity could distinguish Chinese children with dyslexia from typically developing children. Sixteen children with dyslexia and 44 age-matched controls were administered a Cantonese lexical tone perception task, psychoacoustic tasks, a nonverbal reasoning ability task, and word reading and dictation tasks. Children with dyslexia performed worse than controls on Cantonese lexical tone perception, rise time, and intensity. Furthermore, Cantonese lexical tone perception appeared to be a stable indicator that distinguishes children with dyslexia from controls, even after controlling for basic auditory processing skills. These findings suggest that suprasegmental phonological processing (i.e., lexical tone perception) is a potential factor that accounts for reading difficulty in Chinese.